Mental Health Outcomes Among Post-Pandemic Populations: A Longitudinal Analysis - Lubna Yaqoob (Global Journal of Multidisciplinary and Applied Sciences, 2025)
The COVID-19 pandemic produced profound and long-lasting psychological consequences globally, particularly in populations exposed to prolonged stress, social isolation, and economic uncertainty. This longitudinal analysis examines mental health outcomes—including anxiety, depression, PTSD, and behavioral changes—across post-pandemic populations over a three-year period. Data from community-based cohorts reveal persistent psychological distress, delayed recovery patterns, and significant demographic disparities. The study highlights the need for culturally sensitive interventions, improved mental health infrastructure, and long-term monitoring. Findings emphasize the importance of precision mental health strategies, integrating digital care models, and strengthening resilience frameworks in vulnerable communities.